2022
DOI: 10.1007/s00464-022-09233-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific stomach biomechanics before and after laparoscopic sleeve gastrectomy

Abstract: Background Obesity has become a global epidemic. Bariatric surgery is considered the most effective therapeutic weapon in terms of weight loss and improvement of quality of life and comorbidities. Laparoscopic sleeve gastrectomy (LSG) is one of the most performed procedures worldwide, although patients carry a nonnegligible risk of developing post-operative GERD and BE. Objectives The aim of this work is the development of computational patient-specific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The authors also highlighted how the future use of the methods of bioengineering has the potential to increase the success of surgeries and to improve the performances, in general, of the surgical procedures and, in particular, of currently existing ASs, leading to the development of more reliable and durable devices. [23][24][25] The results of this systematic review were reported in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Using databasespecific subject headings, SCIENCEDIRECT, PUBMED, GOOGLE SCHOLAR, GOOGLE PATENTS were searched from inception until May 2022.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The authors also highlighted how the future use of the methods of bioengineering has the potential to increase the success of surgeries and to improve the performances, in general, of the surgical procedures and, in particular, of currently existing ASs, leading to the development of more reliable and durable devices. [23][24][25] The results of this systematic review were reported in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Using databasespecific subject headings, SCIENCEDIRECT, PUBMED, GOOGLE SCHOLAR, GOOGLE PATENTS were searched from inception until May 2022.…”
mentioning
confidence: 72%
“…Furthermore, an evaluation of well‐established ASs has been conducted by considering the clinical outcomes of several studies, highlighting the response of the biological tissues to the presence and the occluding action of ASs, finding that ASs revisions are due to the failure of the device, or to the establishment of degeneration phenomena in the tissues involved by the device's action. The authors also highlighted how the future use of the methods of bioengineering has the potential to increase the success of surgeries and to improve the performances, in general, of the surgical procedures and, in particular, of currently existing ASs, leading to the development of more reliable and durable devices 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…reduction in the size of the stomach through a partial gastrectomy) used in the treatment of patients with obesity, on the biomechanics of the GI organs (Toniolo et al. 2022 ), with one aim being to have patient-specific pre- and post-operative computational models of the organ prior to the procedure to provide a means to assess the best surgical intervention and predict potential post-procedural complications. Moreover, surgical simulations are a growing technology which can utilise FE models to provide haptic force feedback information to a surgeon (Chakravarthy et al.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models allow the investigation of anatomical districts in both healthy and pathologic conditions, providing information about the biomechanical functionality and the effects of pathologies [11,49,50]. Furthermore, the computational approach entails the possibility of analyzing many different diagnostic and surgical procedures, providing tools for the investigation of the interaction phenomena with devices and prostheses and for the evaluation of post-surgical functionality [8,10,49,51,52].…”
mentioning
confidence: 99%